Snakebites in the Mato Grosso State, Brazil: from 2007 to 2019 - Silva , Carlos Eduardo Reis; Paese , Márcia Carolina de Siqueira; Alegranci, Pâmela (Scientific Electronic Archives, 2021)
Snakebites are considered a serious public health problem due to its incidence and severity; in 2017 it was considered a neglected tropical disease. Mato Grosso state have a large territorial extension, composed by a tropical forest and semi-humid climate, and this could contributed for accidents with snakes, principally in rural areas. Regarding the state, epidemiological studies of accidents with snakes are scarce, so the present study aimed to evaluate the clinical-epidemiological aspects of snakebites in Mato Grosso state from 2007 to 2019. It was a retrospective descriptive study with data obtained from the Health Information Notification System (SINAN). In the analyzed period, there were 13,754 cases of snakebites, 90.77% were caused by Bothrops genus. The profile of individuals were male with age from 20 to 59 years old. The time that had elapsed between the accident and care being administered in 66.19% of the cases was up to 3 hours, the cases were considered mild or moderated (86.76%) with 89.25% evolution to cure. The incidence rate varied from 41.2 (in 2010) to 25.4 (in 2018) cases per 100,000 inhabitants with a central tendency to reduction of the cases over the years, and according to the macro-regions were observed higher incidences in East. Future investigations are necessary to explain the variation of incidence according to the macro-regions of Mato Grosso state.